"He likes playing the hero – I let her have fun shooting". Gender games in the Italian forest during the hunting season. (August 2018) - Giacomelli, Stefano; Gibbert, Michael
Highlights: Men and women coproduce their hunting experience in the forest. Men accept women during hunting trips because it allows them to exercise traditional gender roles without reproach. Women accept the subjugation to men's hegemony as a means to not lose social legitimacy in their new domain.